2010
DOI: 10.1080/08870440902736964
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of health: Education and health-related behaviours partially mediate the relationship between conscientiousness and self-reported physical health

Abstract: The personality trait of conscientiousness is an important predictor of health and longevity. The present research examined how conscientiousness, in combination with educational attainment and health-related behaviours, predicted self-reported physical health across adulthood. These relations were investigated in two studies, one using a large, representative sample of Illinois residents (N = 617) and the other using a community sample with a multi-method assessment of conscientiousness (N = 274). Across both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(110 citation statements)
references
References 35 publications
6
102
0
2
Order By: Relevance
“…In our analysis, smoking, alcohol/substance misuse, and hypertension and hypercholesterolemia (biological consequences of poor diet and exercise) accounted for trivial portions of the observed effect, consistent with prior findings that health behaviors account for only a modest portion of the association between conscientiousness and health outcomes (39, 40). One suggestion is that conscientiousness people may enjoy better immune functioning (41), perhaps because their approach to life reduces stress (42, 42).…”
Section: Resultssupporting
confidence: 89%
“…In our analysis, smoking, alcohol/substance misuse, and hypertension and hypercholesterolemia (biological consequences of poor diet and exercise) accounted for trivial portions of the observed effect, consistent with prior findings that health behaviors account for only a modest portion of the association between conscientiousness and health outcomes (39, 40). One suggestion is that conscientiousness people may enjoy better immune functioning (41), perhaps because their approach to life reduces stress (42, 42).…”
Section: Resultssupporting
confidence: 89%
“…Lodi-Smith et al (2010) reported that, across two cross-sectional samples, C predicted self-rated health in adulthood by way of education and preventive behaviors (e.g., regular medical examinations and obeying traffic rules). These mediational patterns were observed controlling for a path from education to preventive behaviors, suggesting that the C-education-health pathway includes preventive or risky behaviors, but other mechanisms as well.…”
Section: Socioeconomic Attainmentsmentioning
confidence: 99%
“…Personality traits predict longevity across many decades (Jackson et al, 2015) and prospectively predict disease onset (Jokela et al, 2013;Weston, Hill & Jackson, 2014). The intervening mechanisms linking personality to these outcomes are largely health behaviors and stress (Hampson et al, 2015;Lodi-Smith et al, 2010).…”
mentioning
confidence: 99%